2022
DOI: 10.1039/d2cp02541h
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric, spin-dependent optical and quantum transport properties of 2D half-metallic Co2Se3

Abstract: In this paper, the thermoelectric, spin-dependent optical and quantum transport properties of two-dimensional(2D) Co2Se3 monolayer are investigated using first principle calculations. The stability of Co2Se3 monolayer is confirmed by energy-cohesive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Figure 3a shows the current-voltage (I-V) curves of CoTe fieldeffect transistor from 5 to 300 K. The nonlinear I-V curves exhibit reduced current density at lower temperature. A negative gate voltage (Figure 3b) increases the channel current, suggesting the p-type semiconductor of CoTe nanostructure prepared from the [ 32] 1: semiconducting (nano-size or quantum dot) [ 96] ; 2: metallic, 1.8×10 6 S/m (film) [98] 1: semiconducting [34] ; 2: metallic [ 76] nonmetallic [ 57] saturation magnetization 37.38 emu/g [33] 0.38 emu [ 58] weak ferromagnetism [34,76] ∼10 emu/g [ 57] 7.52 emu/g [ 81] paramagnetic [ 58,83] 13.4 emu/g [ 83] others 1: low overpotential [ 16] ; 2: ferrimagnetic [ 81] 1: Dirac fermiology [ 24] ; 2: temperature-dependent emission [ 30] ;…”
Section: Magnetic and Ferromagnetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3a shows the current-voltage (I-V) curves of CoTe fieldeffect transistor from 5 to 300 K. The nonlinear I-V curves exhibit reduced current density at lower temperature. A negative gate voltage (Figure 3b) increases the channel current, suggesting the p-type semiconductor of CoTe nanostructure prepared from the [ 32] 1: semiconducting (nano-size or quantum dot) [ 96] ; 2: metallic, 1.8×10 6 S/m (film) [98] 1: semiconducting [34] ; 2: metallic [ 76] nonmetallic [ 57] saturation magnetization 37.38 emu/g [33] 0.38 emu [ 58] weak ferromagnetism [34,76] ∼10 emu/g [ 57] 7.52 emu/g [ 81] paramagnetic [ 58,83] 13.4 emu/g [ 83] others 1: low overpotential [ 16] ; 2: ferrimagnetic [ 81] 1: Dirac fermiology [ 24] ; 2: temperature-dependent emission [ 30] ;…”
Section: Magnetic and Ferromagnetic Propertiesmentioning
confidence: 99%
“…Similarly, intense progress in expanding the border of Co x Te y in the aspects of piezoelectric and electronic properties was also made in the last decade. [23,24,76,77] In this section, the mechanism, reinforcement and advance of Co x Te y 's properties, especially in 2D limit, will be individually overviewed.…”
Section: Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Huang et al demonstrated the existence of an intrinsic long-range magnetic order in two-dimensional materials by successfully synthesizing single-layer CrI 3 with a T C of 45 K, which was followed by extensive studies to find 2D nanosheets with more practical magnetic properties . MnSe 2 , CrTe 2 , VSe 2 , and CrSe 2 are some of the TMC magnetic nanosheets that have been successfully synthesized. Also, the magnetic properties of Cr 2 Te 3 , Cr 2 S 3 , Co 2 S 2 , and Co 2 Se 3 nanosheets have been predicted using first-principles calculations. According to the oxidation states of transition metals, they can exhibit various magnetic states in combination with other elements. For example, 2D CrO 2 and 2D Cr 2 O 3 nanosheets are a half-metallic ferromagnetic and a ferromagnetic semiconductor with Curie temperatures of 686 and 332 K, respectively, which can be used in spintronic devices due to their high T C and large magnetic anisotropy energy (MAE). 2D structures of cobalt telluride are magnetic nanosheets with different stoichiometries.…”
Section: Introductionmentioning
confidence: 99%
“…MnSe 2 , CrTe 2 , VSe 2 , and CrSe 2 are some of the TMC magnetic nanosheets that have been successfully synthesized. Also, the magnetic properties of Cr 2 Te 3 , Cr 2 S 3 , Co 2 S 2 , and Co 2 Se 3 nanosheets have been predicted using first-principles calculations. According to the oxidation states of transition metals, they can exhibit various magnetic states in combination with other elements. For example, 2D CrO 2 and 2D Cr 2 O 3 nanosheets are a half-metallic ferromagnetic and a ferromagnetic semiconductor with Curie temperatures of 686 and 332 K, respectively, which can be used in spintronic devices due to their high T C and large magnetic anisotropy energy (MAE). 2D structures of cobalt telluride are magnetic nanosheets with different stoichiometries. Negedu et al successfully synthesized 2D CoTe, CoTe 2 , and Co 2 Te 3 layers using the liquid-phase exfoliation method.…”
Section: Introductionmentioning
confidence: 99%